Effects of information and price promotions on farmer experimentation with new maize hybrids - Kariuki, Sarah Wairimu; Muteti, F.N.; Donovan, Jason; Rutsaert, Pieter; Ndegwa, Michael Kariuki; Mbugua, Mercy (Elsevier, 2025)
Varietal turnover in maize seed systems in sub-Saharan Africa remains slower than expected, despite significant public and private investment in breeding and seed commercialization. Encouraging farmers to experiment with new hybrids could accelerate adoption and facilitate the replacement of outdated seed products. This study evaluates the impact of point-of-sale information and price promotions on farmer purchases of new maize hybrids in Kenya, using a randomized controlled trial with 1,790 farmers intercepted at agro-dealer shops. We tracked farmers' seed choices immediately after the intervention and again in the following season, eight months later. Informational messages that highlighted the benefits of new hybrids and recommended specific hybrids increased the likelihood that farmers purchased these seeds. Combining information with a price discount increased both the likelihood of purchase and the quantity of seed bought. Follow-up data show that discount-induced experimentation translated into continued use, suggesting that farmers were willing to pay full price after the initial trial. These findings underscore the potential of modest targeted retail interventions to overcome adoption frictions and accelerate varietal turnover.